Determinants of Adoption of New Technology in Telecom Sector: A Structural Equation Modeling Approach. Issue 1 (February 2019) - Chatterjee, Susmita; Chaudhuri, Bibek Ray; Dutta, Debabrata
In this article, we look at the determinants of the new technology adoption by consumers in the case of mobile telecommunications. The dynamic nature of the telecom industry is a result of the frequent technological change. Consumers witness different technology standards in mobile communications, starting from the first generation (1G) to second generation (2G) subsequently to third (3G) and now experiencing fourth (4G) in some countries such as Norway, Sweden, South Korea, and the USA including ours. The movement from one standard to the other has been predicted to be smooth as all of them are vertical substitutes for each other. Given the various dimensions such as price, requirements, utility and so on, these technology standards are not perfect substitutes. The article investigates the prospect of a new technology standard roll out in India. A survey of 400 mobile phone customers in metro telecom circles has been carried out for this purpose. The study applies structural equation modeling (SEM) and explores the adoption intention of this new technology among the respondents. Results show that the presence of low-cost alternatives that is the availability of a lower technology standard poses a significant hurdle to the adoption of new technology services.